Perwujudan Cinta Tanah Air melalui Doa, Ungkapan, dan Lagu dalam Perayaan Ekaristi - Antonius P Sipahutar; Sarumaha, Firmina Novrizab; Obe, Alexius Poto (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
This study is based on the conviction that love for one’s homeland is an integral part of Christian faith, which must be lived out concretely in national and social life. The Catholic Church in Indonesia affirms that patriotism is not merely a moral or political attitude, but an expression of faith manifested through prayer, symbols, and songs within the celebration of the Eucharist. The purpose of this study is to explore how the value of love for the homeland is embodied and expressed liturgically as a contextual form of Catholic faith. This research employed a library research method by examining official Church documents as well as relevant theological and pastoral literature. The analysis was carried out through a descriptive-theological approach that integrates conceptual and contextual perspectives. The findings reveal that love for the homeland in the Eucharistic celebration is manifested through thanksgiving prayers for the nation, the inculturation of national symbols, and the use of patriotic hymns as expressions of faith and gratitude. The Eucharist serves as a sacred meeting point between faith and nationhood, forming believers to be faithful Catholics and true citizens. The study implies that liturgical inculturation plays a vital role as a medium of faith formation and national character building within the Indonesian Catholic Church.